Representasi Konflik Keluarga Anak Tunggal dengan Ibu pada Film Ali dan Ratu-Ratu Queens - Fikri Firdaus; Wiki Angga Wiksana (UNISBA Press, 2023)
Abstract. If there is a conflict that has not been resolved in a family relationship, it will have a negative impact on the people around it. The closest person around is a child. The development experienced by the child is very easily influenced by the surrounding environment. An environment that is not right for children's growth and development can produce a person who is not good for children. This type of research uses qualitative methods with a symbolic interactionism theory approach. The object of this study is the scene in the film ali and queens queens that contain the conflict of the family of an only child with the mother . The purpose of this study is to describe the symbolic interaction of mind, self and society conflict in the film Ali and Ratu-Ratu Queens. In the study, researchers found the Mind process in Ali's interaction with Mia through gestures, symbols, meanings and actions. The mind obtained is in the form of a symbol during the interaction. Meanwhile, Self went through 3 stages, namely the preparation stage, the playing stage and the game stage. The preparatory stage occurred Ali's desire to see his mother to New York. The play stage begins when Ali asks over the puzzles in his life. The stage of the game when the check symbol that Mia gives to Ali. The society that was found was the existence of family conflicts that occurred in society, the way of thinking of society. Abstrak. Apabila dalam hubungan keluarga terjadi konflik yang belum diselesaikan maka akan berdampak negatif bagi orang disekitarnya. Orang sekitar yang paling terdekat ialah seorang anak. Perkembangan yang dialami oleh anak sangat mudah dipengaruhi oleh lingkungan sekitar. Lingkungan yang kurang tepat bagi tumbuh kembang anak dapat menghasilkan pribadi yang tidak baik bagi anak.. Tipe penelitian ini menggunakan metode kualitatif dengan pendekatan teori interaksionisme simbolik. Objek pada penelitian ini adalah adegan pada film ali dan ratu-ratu queens yang mengandung konflik keluarga anak tunggal dengan ibu . Tujuan penelitian ini adalah untuk mendeskripsikan interaksi simbolik pikiran (mind), diri (self) dan masyarakat (society) konflik pada film Ali dan Ratu-Ratu Queens. Dalam penelitian, peneliti menemukan proses Mind pada interaksi Ali dengan Mia melalui gesture,simbol,makna dan tindakan. Mind yang didapatkan berupa simbol selama interaksi. Sedangkan Self melalui 3 tahapan yaitu tahap persiapan, tahap bermain dan tahap permainan. Tahap persiapan terjadi keinginan Ali untuk menemui ibunya ke New York. Tahap bermain dimulai ketika Ali bertanya atas teka-teki dalam hidupnya. Tahap permainan ketika simbol cek yang diberikan Mia kepada Ali. Society yang ditemukan yaitu adanya konlfik keluarga yang terjadi pada masyarakat, cara berpikir masyarakat.